Controlling Factors Analyses of Sediment Dispersal From Source-to-Sink Systems of Lacustrine Rift Basin: A Case Study From Paleogene Shahejie-Dongying Formations of Nanpu Sag, Eastern China - Yu, Jifeng; Liu, Tianjiao; Jia, Haibo; Jiang, Zihao; Wei, Shuhao; Li, Yanping; Ma, Shibiao (Frontiers in Earth Science, 2021)
Tectonic activity not only shapes the basic stratigraphic framework of rift basins, but also profoundly affects the sediment dispersal in rift basins. In this study, analyses of heavy mineral assemblages in different periods demonstrate that there are three obvious tectono-sedimentary evolutionary stages (Es3–Es2, Es1–Ed2, and Ed1, respectively) in the Paleogene provenance area of Nanpu Sag, and the volume of sand bodies increases from the bottom of the Paleogene Shahejie (Es) Formation to the top of the Dongying (Ed) Formation in Nanpu Sag. Besides, this study comprehensively utilize the analyses of seismic interpretation, palynology, heavy mineral, and borehole core samples to investigate the controlling factors of sediment dispersal in the rift basin. The assemblages of heavy minerals in different periods reflect the rock composition and catchment area of different provenance areas, and their vertical differences reflect the evolution process of the provenance area and reflect the uplift-denudation process of the provenance area. The results reveal that the synergy of the evolution of tectonic activity and the adjustment of topographical evolution are the main controlling factors of sediment dispersal in Nanpu Sag, while climate change is not the main controlling factor. We conclude that an increased sediment supply rate in the long term reflects the control of tectonic activity on basin topography, rather than climate fluctuations. The differences in morphological modification result in differential sediment dispersal, which is principally related to the differential extrusion of the fault system. The catchment area and provenance distance adjustment is evidenced by the vertical changes of heavy mineral characteristics of single-well and interaction and linkage of boundary faults, and the adjustment of topography evolution. A consideration is that the interaction and linkage of boundary faults and complex subsidence history are multi-directional, and differential evolution of provenance area is universal in lacustrine rift basins, all of this highlights the adjustment of sediment pathways generated by this characteristic of rift basins and emphasizes the importance of controlling factors analyses in understanding differential sediment dispersal that presents in the rift basins. Besides, four sets of sediment dispersal patterns were delineated based on different developmental regions in the rift basin, which are fault segmental point and multi-stage fault terrace, single-stage fault terrace and axial fault valley, axial fault terrace, and paleo-terrace and axial fault valley, respectively. This study has a certain guiding significance for the prediction of the spatial distribution of sand bodies in the rift basin and the exploration of potential oil and gas targets in the rift basin.